Small item storage demonstration - Unidentified photographer (Colorado State University. Libraries, 2000)
Photograph of Jeanne Brako demonstrating to Jennifer Kutzik and an unidentified woman how to store hats and other small items during an April 2000 workshop. Brako is standing next to a table where the two women are sitting. There are storage supplies on the table.
Keywords: Fashion -- History; Fashion -- Exhibitions